Charlie and the chocolate factory - Dahl, Roald; Blake, Quentin (New York : Puffin Books, 2016)
Each of five children lucky enough to discover an entry ticket into Mr. Willy Wonka's mysterious chocolate factory takes advantage of the situation in his own way.
Keywords: Humorous stories; Behavior -- Fiction